UNDERSTANDING LANGUAGE REVITALIZATION STRATEGIES IN INDIGENOUS LANGUAGE SCHOOLS IN NORTHWEST AREA OF THE UNITED STATES - Kusumaningsih, Sisilia Novena (UC Journal: ELT, Linguistics and Literature Journal, 2022)
The expansion of globalization and the demand to establish one lingua franca for international communication has brought a significant impact on the decline of local languages around the globe. This issue calls for language revitalization programs so that all the Indigenous languages can be passed on to the younger generations. This small-sample-qualitative study describes the strategies used by Indigenous language schools in the Northwest area of the United States and further elaborating on the unique elements of those strategies. Five websites covering the information on Indigenous language school programs in Kalispell, Inchelium, Spokane, Browning, and Arlee were analyzed. In general, schools emphasize the relationality between elders, community, and educational institutions to preserve the language successfully. In addition, technology was utilized to help younger generations access materials more easily. This connection was built through creating listening materials by recording and transcribing the remaining fluent speakers, recording songs and lullabies, introducing Indigenous languages through storybooks, and launching mobile-friendly language apps.